Thomas Hardy selected poems including the complete text of Chosen Poems of Thomas Hardy - Hardy, Thomas, 1840-1928; Bromwich, David, 1951- (New Haven Yale University Press, 2023)
A generous selection of poems by a major Victorian writer, a virtuoso of traditional forms who came to be recognized as a uniquely inventive and original voice in modern poetry This selection of poems by Thomas Hardy (1840-1928), edited by David Bromwich, covers the range of Hardy's extraordinary work: songs, ballads, and sonnets, dramatic monologues and elegies, along with poems that mark epochal events, such as the end of the Great War. This selection shows why Hardy has been admired as the most inward and personal of the moderns, yet also the most accessible and widely read. Included here is the full and integral text of Chosen Poems of Thomas Hardy, the final selection of his own work that Hardy chose to publish. Bromwich has selected more than one hundred fifty additional poems that cover the length of Hardy's career, from Wessex Poems to Winter Words. His critical and biographical introduction sets Hardy's achievement in the context of a career in prose and poetry that has no parallel.
Includes bibliographical references and index
Description based on print version record
In English.
JSTOR
Keywords: English poetry -- 19th century; English poetry -- 20th century; Poésie anglaise -- 19e siècle.; Poésie anglaise -- 20e siècle.; Poetry -- English, Irish, Scottish, Welsh; Literary Criticism -- Poetry; English poetry; 1800-1999; Poetry; poetry; Poetry; Poetry; Poésie.